Über ein System der Differentialgleichungen, das in geschlossener form integrierbar ist - Merkys, V.; Akucevičiūtė, N. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Меркис, Н. М. Акуцевичюте. Об одной системе дифференциальных уравнений, интегрируемой в конечном видеV. Merkys, N. Akucevičiūtė. Apie vieną diferencialinių lygčių sistemą, integruojamą baigtiniu pavidalu